In their Own Words: Exploring Students’ Perspective on Accessing Assistive Technologies in a Blind School - Devi, Sarita; Ingole, Meenakshi R. (Indian Journal of Educational Technology, 2025)
Assistive technologies are pivotal in enhancing the daily lives of students with visual impairments (SVIs), facilitating activities such as orientation, mobility, reading, writing, and exploring their surroundings. This study adopts a qualitative case study approach to investigate the availability of assistive technologies at a blind school in Delhi and understand the perspective of SVIs towards accessing these technologies. Participants in the study include middle school students aged 12-18 years. Primary data is gathered through observations, unstructured interviews, and conversations, complemented by secondary data from relevant literature. The data is analyzed thematically by categorizing it using an iterative reflective process. The results indicate a prevalence of traditional assistive technologies in schools, including Braille Slate, Stylus, Braille Books, and Taylor Frame for Arithmetic. Students exhibit a preference for these traditional tools, finding them more comfortable. Nevertheless, smartphones are concurrently utilized to stimulate academic and leisure interests. The study highlights the limited reach of various assistive technologies at the grassroots level. Students’ engagement with traditional assistive technologies and smartphones for learning introduces an intersubjective dimension, rendering them more preferable to alternative options